A Lewis Base Catalysis Approach for the Photoredox Activation of Boronic Acids and Esters. (24th October 2017) - Lima, Fabio; Sharma, Upendra K.; Grunenberg, Lars; Saha, Debasmita; Johannsen, Sandra; Sedelmeier, Joerg; Van der Eycken, Erik V.; Ley, Steven V.
Abstract: We report herein the use of a dual catalytic system comprising a Lewis base catalyst such as quinuclidin‐3‐ol or 4‐dimethylaminopyridine and a photoredox catalyst to generate carbon radicals from either boronic acids or esters. This system enabled a wide range of alkyl boronic esters and aryl or alkyl boronic acids to react with electron‐deficient olefins via radical addition to efficiently form C−C coupled products in a redox‐neutral fashion. The Lewis base catalyst was shown to form a redox‐active complex with either the boronic esters or the trimeric form of the boronic acids (boroxines) in solution.